(untitled) (Bangladesh Journal of Medical Science, 2015)
A 28 days old neonate presented with high fever, abdominal distension, poor feeding and lethargy. Sepsis screen was positive; ultrasound and computed tomography of the abdomen demonstrated a multiloculated hepatic abcess in the right lobe of the liver. The baby was treated with intravenous antibiotics for 6 weeks and percutaneous aspiration of the abcess, resulting in excellent recovery. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.299-301